Managerial Ownership and Accounting Conservatism - LAFOND, RYAN; ROYCHOWDHURY, SUGATA (Journal of Accounting Research, 2008)
ABSTRACT In this paper we examine the effect of managerial ownership on financial reporting conservatism. Separation of ownership and control gives rise to agency problems between managers and shareholders. Financial reporting conservatism is one potential mechanism to address these agency problems. We hypothesize that, as managerial ownership declines, the severity of agency problem increases, increasing the demand for conservatism. Consistent with our hypothesis, we find that conservatism as measured by the asymmetric timeliness of earnings declines with managerial ownership. The negative association between managerial ownership and asymmetric timeliness of earnings is robust to various controls, in particular, for the investment opportunity set. We thus provide evidence of a demand for conservatism from the firm's shareholders.